2004
DOI: 10.1590/s0100-879x2004000100012
|View full text |Cite
|
Sign up to set email alerts
|

Estrogen and progesterone receptors in human papilloma virus-related cervical neoplasia

Abstract: Estrogen (ER) and progesterone (PR) receptors in the normal uterine cervix, cervical intraepithelial neoplasia and invasive carcinoma were studied in consecutive samples from Hospital do Câncer, São Paulo, between 1996 and 1997. Tissue was collected by removing a fragment of the tumoral area using a 5-mm diameter biopsy punch, followed by removal of a macroscopically normal area as close as possible from the tumor. Histopathological confirmation was obtained for all specimens analyzed. A total of 24 normal tis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
14
0
3

Year Published

2006
2006
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(21 citation statements)
references
References 18 publications
2
14
0
3
Order By: Relevance
“…Zhai and coworkers (Zhai et al 2010) have also observed a loss of ERα expression during CC progression starting from CIN I and CIN II/III and continuing to invasive squamous cell carcinoma with 50, 15 and 3.7% ERα positivity, respectively. In normal cervical tissue, Zhai and coworkers have observed 77% of ERα positivity, which is in line with the pattern observed by Coelho and coworkers (Coelho et al 2004). Zhai and coworkers have also noted that there is no correlation between HPV status or HPV type with the loss of ER expression, which is contrary to Nonogaki and coworkers.…”
Section: Studies Using Clinical Specimens Indicate a Differential Erαsupporting
confidence: 86%
See 4 more Smart Citations
“…Zhai and coworkers (Zhai et al 2010) have also observed a loss of ERα expression during CC progression starting from CIN I and CIN II/III and continuing to invasive squamous cell carcinoma with 50, 15 and 3.7% ERα positivity, respectively. In normal cervical tissue, Zhai and coworkers have observed 77% of ERα positivity, which is in line with the pattern observed by Coelho and coworkers (Coelho et al 2004). Zhai and coworkers have also noted that there is no correlation between HPV status or HPV type with the loss of ER expression, which is contrary to Nonogaki and coworkers.…”
Section: Studies Using Clinical Specimens Indicate a Differential Erαsupporting
confidence: 86%
“…Masood and coworkers demonstrated ERα (30%) and PR (35%) positivity in adenocarcinoma specimens, and this positive expression status correlated with prolonged patient survival (Masood et al 1993). Contrary to the above statement, the loss of ERα expression was established as an early alteration during the progression of cervical dysplasia to invasive carcinoma (Nonogaki et al 1990, Konishi et al 1991, Coelho et al 2004, Zhai et al 2010, López-Romero et al 2013, Nikolaou et al 2014. The majority of the basal cells in normal cervical tissue stained positive for ERα, whereas the percentage of ERα expression was decreased in CIN and squamous cervical carcinoma to 31% and 11%, respectively (Nikolaou et al 2014).…”
Section: Studies Using Clinical Specimens Indicate a Differential Erαmentioning
confidence: 98%
See 3 more Smart Citations